The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s15010-007-6316-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multiresistance of Gram-negative Bacteria in Bloodstream Infection on Mortality Rates and Length of Stay

Abstract: Multiresistance of GNB causing BSI was associated with higher mortality rates and longer LOS in ICU. The initial antibiotic therapy was significantly more often inadequate and might have had an impact on overall mortality. Thus, an effective strategy to administer an appropriate initial empirical antibiotic therapy, especially in patients with risk factors, must be sought. Moreover, the overall usage of antimicrobials must be limited and infection control guidelines should be followed to reduce the emergence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 30 publications
2
30
1
5
Order By: Relevance
“…Infections with resistant strains are a major concern because they increase the risk of therapeutic failure [18,19] and are associated with secondary bacteraemia [20] and a considerable increase in mortality, length of hospital stay and overall health costs [9,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Infections with resistant strains are a major concern because they increase the risk of therapeutic failure [18,19] and are associated with secondary bacteraemia [20] and a considerable increase in mortality, length of hospital stay and overall health costs [9,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the Gram-negative bacilli carriers had a high length of stay (mean: 37.2 days). The prolonged length of stay in health institutions and the antimicrobials used may increase the risk of multidrug-resistant microorganisms acquisition [23] [24].…”
Section: Discussionmentioning
confidence: 99%
“…7,[23][24][25][26] However, there are studies showing no significant impact of antibiotic resistance on mortality. 27 FI GU RE 1: Kap lan-Me i er sur vi val es ti ma tes by su i ta bi lity of the tre at ment.…”
Section: Discussionmentioning
confidence: 99%